BOOK REVIEWS (Journal of Finance, 1976)
Book reviewed in this article: Optimization of Bank Portfolios . By W illiam F. B eazer . Bank Management and Portfolio Behavior . By D onald D. H ester and J ames L. P ierce . Pension Funds and Other Institutional Investors . By E dward M alca . Interest Rates on Savings Deposits . By M ryon B. S lovin and M arie E. S ushka . Business Financial Management . By G eorge N. E ngler . Preference Shares and Company Finance . By L. C. G upta . Corporate Planning and Control Model Systems . By A kira I shikawa . Financial Planning in the Indian Public Sector: A Management Approach . By B. S. S harma . Accounting for the Cost of Interest . By R obert N. A nthony . Efficient Capital Markets and Accounting: A Critical Analysis . By T homas R. D yckman , D avid H. D ownes , and R obert P. M agee . Theory of Accounting Measurement . By Y uji I jiri . Financing Anglo–American Trade: The House of Brown, 1800–1880 . By E dwin J. P erkins .